PENGARUH CRM DAN PROMOSI TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN UMKM LAUNDRY QIWA - Hasan, Golan; Wibawa, Aria; Armando, Pandapotan Rafli; Ricky, Ricky (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study analyzes the effect of price and promotion on customer satisfaction and loyalty at MSME Laundry QIWA in Batam. For five years, QIWA Laundry has built loyalty through competitive pricing strategies and promotions, such as shuttle services and discounts. The study aims to identify the role of customer satisfaction as a mediator between price, promotion, and customer loyalty to maintain competitiveness in the laundry market. A qualitative approach was used with in-depth interviews and participatory observation, as well as purposive sampling techniques to select respondents. The main variables include price, promotion, customer satisfaction as mediation, and loyalty as dependent variable. The results show that competitive pricing and attractive promotions increase customer satisfaction, which in turn plays a significant role in increasing loyalty. Satisfied customers are more likely to return to use QIWA Laundry services and recommend it to others, confirming the close relationship between customer satisfaction and loyalty